2005
DOI: 10.1002/ijc.20956
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and use of papanicolaou test among HIV‐positive women

Abstract: Dear Sir,It is well known that women who are infected with the human immunodeficiency virus (HIV) have higher rates of infection with human Papillomaviruses (HPV) 1,2 and that these women present an approximately 10-fold higher risk for invasive cervical cancer (ICC) than age-matched women in the general population. 3 In addition to the high frequency of HPV infection, the increased ICC risk in HIVpositive women could be explained by the immunosuppressive effect of HIV, which may accelerate HPV-related oncogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
(7 reference statements)
3
2
1
Order By: Relevance
“…Conversely, receiving screening advice from a gynecologist significantly improved the adherence to Pap-smear. We found less influence of education level or country of birth than a previous cross-sectional study conducted in Rome [13]. As expected, study women reported a high proportion of previous abnormal Pap-smears (34%), in agreement with previous reports among HIV-positive women in Italy [13] and the United States [8,9].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Conversely, receiving screening advice from a gynecologist significantly improved the adherence to Pap-smear. We found less influence of education level or country of birth than a previous cross-sectional study conducted in Rome [13]. As expected, study women reported a high proportion of previous abnormal Pap-smears (34%), in agreement with previous reports among HIV-positive women in Italy [13] and the United States [8,9].…”
Section: Discussionsupporting
confidence: 90%
“…These proportions are similar to the ones reported by the general population of the same age and geographical area (95% and 47%, respectively) (Carrozzi and Bertozzi, personal communication), and substantially higher than those reported (43%) in 2001 by a physician-based Italian survey [14]. Increase in the number of Pap-smears performed, however, is difficult to evaluate, given the different study designs of previous studies conducted in Italy [13,14]. The proportion of women who had a Pap-smear in the last year, however, remains suboptimal with respect to current guidelines regarding HIV-positive women (annual Pap-smear recommended to all patients), and is lower than the estimates (approximately 80%) reported in the USA [8,9].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Studies have also shown that women with a history of STIs and/or pregnancy, which may correlate with number of sexual partners, are more likely to undergo Pap screening [28,33]. Having acquired HIV heterosexually was also associated with better adherence to Pap testing (OR 3.2); this is in keeping with multiple other studies, which have determined that women who acquire HIV perinatally [33], and women who use intravenous drugs [8,24,26,36,53], have poorer screening rates than those who acquire HIV through sexual intercourse with a male.…”
Section: Discussionsupporting
confidence: 83%
“…The association between older age and lack of Pap testing may be related to the misconception that Pap testing is no longer necessary after menopause [20,52]. Sadly, there is a linear relationship between diagnosis of cervical cancer and age [44,48,53], with most deaths from invasive cervical cancer occurring in those over the age of 50 years [54]; therefore continued Pap testing in older women is essential.…”
Section: Discussionmentioning
confidence: 99%